Culture, cC/mmunication & Ideology = Forms of Work - Fuchs, Christian (Media and left)

Synthesis of mesoporous alumina through photo cross-linked poly(dimethylacrylamide) hydrogels - Birnbaum, Wolfgang; Weinberger, Christian; Schill, Verena; Haffer, Stefanie; Tiemann, Michael; Kuckling, Dirk (Colloid and Polymer Science)
Catalysis plays a central role in many fields of life, e.g., in biochemical processes, to reduce energy costs and resources in chemical industry and to decrease or even avoid environmental pollution and in energy management. Porous alumina (Al2O3) is an essential material in various applications, especially as a support material for catalysts. It is often prepared by nanocasting using porous carbon materials that serve as rigid structure matrices. In this work, an alternative way to synthesize mesoporous Al2O3 by using hydrogels as porogenic material is presented. Hydrogels can easily be patterned by light and used to imprint their structure onto alumina opening a new approach to fabricate patterned Al2O3. The hydrogels used in this work are based on poly(dimethylacrylamide) and were photo-chemically cross-linked. Followed by a nanocasting process, mesoporous alumina samples were synthesized and characterized by N2 physisorption and X-ray diffraction. The cross-linker amount in the polymer network was varied and the influence on the properties of the Al2O3 is analyzed.

A synthesis concept for a nanostructured CoFe2O4/BaTiO3 composite: Towards multiferroics - Haffer, Stefanie; Lüder, Christian; Walther, Till; Köferstein, Roberto; Ebbinghaus, Stefan G.; Tiemann, Michael (Microporous and Mesoporous Materials)
The synthesis of a periodically ordered, nanostructured composite consisting of CoFe2O4 and BaTiO3 is presented. In a first step, mesoporous CoFe2O4 is prepared by the structure replication method (nanocasting) using mesoporous KIT-6 silica as a structural mold. Subsequently, BaTiO3 is created inside the pores of CoFe2O4 by the citrate route, resulting in a well-ordered composite material of both phases. The two components are known for their distinct ferroic properties, namely ferrimagnetism (CoFe2O4) and ferroelectricity (BaTiO3), respectively. Therefore, this proof of synthesis concept offers new perspectives in the fabrication of composite materials with multiferroic properties.

One-step synthesis of multi-modal pore systems in mesoporous In2O3: A detailed study - Klaus, Dominik; Amrehn, Sabrina; Tiemann, Michael; Wagner, Thorsten (Microporous and Mesoporous Materials)
Ordered mesoporous silica phases (e.g. KIT-6, SBA-15) are used as structure matrices for negative replica structures of mesoporous In2O3. We present a detailed study on how the controlled synthesis of mono-, bi- and trimodal pore systems in the products is accomplished by systematic variation of the procedure of infiltrating a precursor species (In(NO3)3) into the pores of the silica matrix and subsequent thermal conversion into In2O3. Melt impregnation and conversion in a closed reactor facilitates a one-step casting process for ordered mesoporous indium oxide (In2O3). We present a model based on variation of the pore filling.

New Sensing Model of (Mesoporous) In2O3 - Wagner, Thorsten; Donato, Nicola; Tiemann, Michael (Springer Series on Chemical Sensors and Biosensors)
Recently indium oxide (In2O3) attracted attention as a material for sensing layers in semiconducting gas sensors. Compared to frequently investigated materials like tin dioxide (SnO2), tungsten trioxide (WO3), or gallium oxide (Ga2O3) indium oxide offers some unique properties. The most prominent one is its selectivity to oxidizing gases such as ozone (O3) or nitrogen dioxide (NO2) at low operating temperatures (<150°C). Combined with the photoreduction properties of nanocast, porous In2O3 highly selective sensing layers with a fast response can be prepared. In some cases even room temperature measurements are possible; therefore this material allows for designing low-power sensors without the need for special sensor substrates (e.g., μ-hotplates). Detailed analysis of the sensing mechanism reveals that known sensing models are not able to describe the observed effects. Therefore a new sensing model for ordered nanoporous In2O3 is presented which will be applicable for nonstructured material too.

Arduino-Based Shield for Resistive Gas Sensor Array Characterization Under UV Light Exposure - Aloisio, D.; Donato, N.; Neri, G.; Latino, M.; Wagner, T.; Tiemann, Michael; Capra, P. P. (Lecture Notes in Electrical Engineering)
In this paper, the development and validation of a shield prototype for resistive sensor array characterization with Arduino UNO, a platform based on ATmega328 microcontroller provided by ATMEL, is reported. The resistance variation of the sensor can be evaluated by properly choosing the capacitance value and by measuring the period (frequency) of a custom inverter-based oscillator. The GUI and the developed firmware are able to perform the real-time monitoring of the sensor responses. The developed shield is able to measure the response of up to six sensors under UV radiation by means of LED devices. First results carried out with resistive sensors based on mesoporous In2O3-based material under UV light exposure are reported.

Fructose as a Precursor for Mesoporous Carbon: Straightforward Solvent-Free Synthesis by Nanocasting - Weinberger, Christian; Haffer, S.; Wagner, T.; Tiemann, Michael (ACS Symposium Series)
Due to their unique properties, ordered mesoporous carbon (OMC) materials prepared by nanocasting have raised great attention in recent years. Their synthesis usually comprises multiple cycles of impregnating a porous structure matrix with an aqueous solution of a suitable precursor, such as sucrose or other, often hazardous, compound. We present a more straightforward variation of this method by using fructose as the precursor compound. By using a solvent-free melt of the precursor, the impregnation requires only a single step. After carbonization by thermal decomposition and removal of the mesoporous silica structure matrix (SBA-15), ordered mesoporous carbon with one (CMK-3) or two (CMK-5) pore modes in two-dimensional, hexagonal symmetry (p6mm) is obtained.

Social Media as Surveillance: Rethinking Visibility in a Converging World - Allmer, Thomas (European Journal of Communication)

Introduction: Philosophers of the World Unite! Theorising Digital Labour and Virtual Work—Definitions, Dimensions, and Forms - Sandoval, Marisol; Fuchs, Christian; Prodnik, Jernej A.; Sevignani, Sebastian; Allmer, Thomas (Special Issue of tripleC: Communication, Capitalism & Critique)

Why privacy is not enough privacy in the context of “ubiquitous computing” and “big data” - Matzner, Tobias (Journal of Information, Communication and Ethics in Society)
Purpose – Ubiquitous computing and “big data” have been widely recognized as requiring new concepts of privacy and new mechanisms to protect it. While improved concepts of privacy have been suggested, the paper aims to argue that people acting in full conformity to those privacy norms still can infringe the privacy of others in the context of ubiquitous computing and “big data”. Design/methodology/approach – New threats to privacy are described. Helen Nissenbaum's concept of “privacy as contextual integrity” is reviewed concerning its capability to grasp these problems. The argument is based on the assumption that the technologies work, persons are fully informed and capable of deciding according to advanced privacy considerations. Findings – Big data and ubiquitous computing enable privacy threats for persons whose data are only indirectly involved and even for persons about whom no data have been collected and processed. Those new problems are intrinsic to the functionality of these new technologies and need to be addressed on a social and political level. Furthermore, a concept of data minimization in terms of the quality of the data is proposed. Originality/value – The use of personal data as a threat to the privacy of others is established. This new perspective is used to reassess and recontextualize Helen Nissenbaum's concept of privacy. Data minimization in terms of quality of data is proposed as a new concept.

Low temperature fabrication of a ZnO nanoparticle thin-film transistor suitable for flexible electronics - Vidor, F.F.; Wirth, G.I.; Hilleringmann, Ulrich (Microelectronics Reliability)
Keywords: Electrical and Electronic Engineering; Surfaces; Coatings and Films; Safety; Risk; Reliability and Quality; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Stability Analysis of a Charge Pump Phase-Locked Loop Using Autonomous Difference Equations - Hangmann, Christian; Hedayat, Christian; Hilleringmann, Ulrich (IEEE Transactions on Circuits and Systems I: Regular Papers)
Keywords: Electrical and Electronic Engineering

Sub-cycle control of terahertz high-harmonic generation by dynamical Bloch oscillations - Meier, Torsten; Schubert, O.; Hohenleutner, M.; Langer, F.; Urbanek, B.; Lange, C.; Huttner, U.; Golde, D.; Kira, M.; Koch, S. W.; Huber, R. (Nature Photonics)
Ultrafast charge transport in strongly biased semiconductors is at the heart of high-speed electronics, electro-optics and fundamental solid-state physics1,2,3,4,5,6,7,8,9,10,11,12,13. Intense light pulses in the terahertz spectral range have opened fascinating vistas14,15,16,17,18,19,20,21. Because terahertz photon energies are far below typical electronic interband resonances, a stable electromagnetic waveform may serve as a precisely adjustable bias5,11,17,19. Novel quantum phenomena have been anticipated for terahertz amplitudes, reaching atomic field strengths8,9,10. We exploit controlled (multi-)terahertz waveforms with peak fields of 72 MV cm−1 to drive coherent interband polarization combined with dynamical Bloch oscillations in semiconducting gallium selenide. These dynamics entail the emission of phase-stable high-harmonic transients, covering the entire terahertz-to-visible spectral domain between 0.1 and 675 THz. Quantum interference of different ionization paths of accelerated charge carriers is controlled via the waveform of the driving field and explained by a quantum theory of inter- and intraband dynamics. Our results pave the way towards all-coherent terahertz-rate electronics.

Adiabatic tracking of quantum many-body dynamics - Saberi, H.; Opatrný, T.; Mølmer, K.; del Campo,, A. (Physical Review A)
The nonadiabatic dynamics of a many-body system driven through a quantum critical point can be controlled using counterdiabatic driving, where the formation of excitations is suppressed by assisting the dynamics with auxiliary multiple-body nonlocal interactions. We propose an alternative scheme which circumvents practical challenges to realize shortcuts to adiabaticity in mesoscopic systems by tailoring the functional form of the auxiliary counterdiabatic interactions. A driving scheme resorting in short-range few-body interactions is shown to generate an effectively adiabatic dynamics.

Von der Öko-Bewegung zur nachhaltigen Entwicklung. Überlegungen zum Verhältnis von kritischem Konsum und Konsumkritik - Hälterlein, Jens (Vielfalt und Zusammenhalt. Verhandlungen des 36. Kongresses der Deutschen Gesellschaft für Soziologie in Bochum und Dortmund 2012)

Privacy Issues in Public Discourse. The Case of 'Smart' CCTV in Germany - Hälterlein, Jens (Privacy and Security in the Digital Age)

One-class genera of maximal integral quadratic forms - Kirschmer, Markus (Journal of Number Theory)
Suppose Q is a definite quadratic form on a vector space V over some totally real field K ≠ Q. Then the maximal integral Zₖ-lattices in (V,Q) are locally isometric everywhere and hence form a single genus. We enumerate all orthogonal spaces (V,Q) of dimension at least 3, where the corresponding genus of maximal integral lattices consists of a single isometry class. It turns out, there are 471 such genera. Moreover, the dimension of V and the degree of K are bounded by 6 and 5 respectively. This classification also yields all maximal quaternion orders of type number one.
Keywords: Algebra and Number Theory

The use of radiation-cured adhesives on adhesive stud assembly process - Meschut, Gerson; Süllentrop, Sebastian (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Hybrid Technologies for Joining Ultra-high-strength Boron Steels with Aluminum Alloys for Lightweight Car Body Structures - Meschut, Gerson; Matzke, Marcus; Hoerhold, Réjane; Olfermann, Thomas (Procedia CIRP)
Keywords: General Medicine

Analysis of Material Behaviour in Experimental and Simulative Setup of Joining by Forming of Aluminium Alloy and High Strength Steel with Shear-Clinching Technology - Müller, Martin; Hörhold, Réjane; Merklein, Marion; Meschut, Gerson (Advanced Materials Research)
In transportation sector the reduction of moving masses without the decrease of safety parameters is a key factor for future economic success. One possible approach for this is the use of different metallic materials in composite construction. Therefore, it is essential to establish a reliable component connection by means of suitable and cost-effective joining technologies. Mechanical joining technologies such as self-piercing riveting and mechanical clinching have proven to be effective methods for joining lightweight materials like aluminium and ductile steels. As these technologies require formability or pre-holing of the joining partners, the field of application is limited by the mechanical properties of the joining partners. Great potential for joining hot stamped steels, which have a very low elongation at fracture and therefore a low formability, offers the shear-clinching technology. For a systematic development of the shear-clinching technology, detailed investigations of the process are required. This paper presents an analysis of the material behaviour during the shear-clinching process and the reference process – clinching with pre-hole.
Keywords: General Engineering

Innovative and Highly Productive Joining Technologies for Multi-Material Lightweight Car Body Structures - Meschut, G.; Janzen, V.; Olfermann, T. (Journal of Materials Engineering and Performance)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Self-pierce Riveting and Hybrid Joining of Boron Steels in Multi-material and Multi-sheet Joints - Hahn, O.; Meschut, G.; Bergau, M.; Matzke, M. (Procedia CIRP)
Keywords: General Medicine

Evaluation of Damage to Carbon-fibre Composites Induced by Self-pierce Riveting - Meschut, G.; Gude, M.; Augenthaler, F.; Geske, V. (Procedia CIRP)
Keywords: General Medicine

Kritische Theorie - Politästhetik - Kunst für alle. Eine Relektüre des praktisch-theologischen Ansatzes Henning Luthers - Schroeter-Wittke, Harald (Henning Luther. Impulse für eine Praktische Theologie der Spätmoderne)

Abgekanzelt - Eine theologische Selbstanzeige. Statement bei der Kabarettveranstaltung "Schluss mit lustig" im Zentrum Kulturkirche (VKUK_016_2029) - Schroeter-Wittke, Harald (Dokumente CD-ROM des 34. DEKT Hamburg 2013)

Performance als religionsdidaktische Kategorie. Prospekt einer performativen Religionspädagogik - Schroeter-Wittke, Harald (Wagnis und Vertrauen. Denkimpulse zu Ehren von Horst-Martin Barnikol)

Kirchenmusik in einem säkularen Umfeld - Schroeter-Wittke, Harald (Der Gottesdienst und seine Musik. Band 2: Liturgik: Gottesdienstformen und ihre Handlungsträger. Enzyklopädie der Kirchenmusik 4/2)

Kirchentage und ihre Gottesdienstformen - Schroeter-Wittke, Harald (Der Gottesdienst und seine Musik. Band 2: Liturgik: Gottesdienstformen und ihre Handlungsträger. Enzyklopädie der Kirchenmusik 4/2)

Wieviel Humor braucht die Kirche? Vortrag auf der Rheinischen Bühne Planten un Blomen - Schroeter-Wittke, Harald (Deutscher Evangelischer Kirchentag Hamburg 2013. Dokumente)

Träume, Wünsche, Sehnsüchte. Schlagertexte im analytischen Blick - Schroeter-Wittke, Harald (Ein bisschen Frieden. Schlager und Kirche im Gespräch)

Auf dieser schiefen Ebene gibt es kein Halten. Leseperformance beim Treffpunkt Oper (VOPA_003_0553) - Schroeter-Wittke, Harald; Arnhold, Oliver; Mattke, Andreas (Dokumente CD-ROM des 34. DEKT Hamburg 2013)

Interview mit einem Bach-Choral. Statement bei der Mitmachrevue Play Bach in der Halle der Kirchenmusik (VKMU_008_2027) - Schroeter-Wittke, Harald (Dokumente CD-ROM des 34. DEKT Hamburg 2013)

Coherent bloch oscillations driven by ultrastrong THz excitation - Meier, Torsten (Frontiers in Optics 2014, OSA Technical Digest)
The carrier wave of high-intensity phase-locked multi-THz pulses controls dynamical Bloch oscillations and interband polarization in bulk semiconductors, leading to the emission of all-coherent high-order harmonics covering 12.7 optical octaves from THz to VIS regimes.

Kirche als Messe - Zum Verhältnis von Deutschem Evangelischem Kirchentag und öffentlichem Raum, dargestellt unter besonderer Berücksichtigung der Kirchentage im Ruhrgebiet - Schroeter-Wittke, Harald (Kirche im Revier)

Tanz und Teufel zusammengedacht. In der christlichen Welt wurde über viele Jahrhunderte hinweg vor dem Tanz gewarnt - Schroeter-Wittke, Harald (Zeitzeichen)

"... denn der Himmel war besetzt." Materialien zu einer Praktischen Theologie des Schlagers - Schroeter-Wittke, Harald (Magazin für Theologie und Ästhetik. http://www.theomag.de/87/hsw16.htm)

Impuls und Design - Friedensklänge aus dem 20. Jahrhundert. Zum 100. Geburtstag von Andrzej Panufnik - Schroeter-Wittke, Harald (Praktische Theologie)

"Das Volk bäumt sich auf in seiner Wut!" Zum 175. Geburtstag von Friedrich Gernsheim - Schroeter-Wittke, Harald (Praktische Theologie)

Mukashi - once upon a time. Zum 80. Geburtstag von Abdullah Ibrahim - Schroeter-Wittke, Harald (Praktische Theologie)

KZ Musik - Schroeter-Wittke, Harald (Praktische Theologie)

CEP control of dynamical Bloch oscillations in a bulk semiconductor via ultra-intense multi-THz fields - Meier, Torsten; Langer, F.; Schubert, O.; Hohenleutner, M.; Urbanek, B.; Lange, C.; Huttner, U.; Golde, D.; Kira, M.; Koch, S.W.; Huber, R. (CLEO: QELS_Fundamental Science)
Dynamical Bloch oscillations and coherent interband polarization in bulk GaSe are controlled by CEP-stable, ultra-intense multi-THz waveforms and result in the emission of phase-stable high-order harmonics covering 12.7 optical octaves from THz to VIS regimes.

Three-dimensional hybrid vortex solitons - Driben, Rodislav; Kartashov, Yaroslav V.; Malomed, Boris A.; Meier, Torsten; Torner, Lluis (New Journal of Physics)
We show, by means of numerical and analytical methods, that media with a repulsive nonlinearity which grows from the center to the periphery support a remarkable variety of previously unknown complex stationary and dynamical three-dimensional (3D) solitary-wave states. Peanut-shaped modulation profiles give rise to vertically symmetric and antisymmetric vortex states, and novel stationary hybrid states, built of top and bottom vortices with opposite topological charges, as well as robust dynamical hybrids, which feature stable precession of a vortex on top of a zero-vorticity soliton. The analysis reveals stability regions for symmetric, antisymmetric, and hybrid states. In addition, bead-shaped modulation profiles give rise to the first example of exact analytical solutions for stable 3D vortex solitons. The predicted states may be realized in media with a controllable cubic nonlinearity, such as Bose–Einstein condensates.

Soliton gyroscopes in media with spatially growing repulsive nonlinearity - Meier, Torsten; Driben, R.; Kartashov, Y. V.; Malomed, B. A.; Torner, L. (Physical review letters)
We find that the recently introduced model of self-trapping supported by a spatially growing strength of a repulsive nonlinearity gives rise to robust vortex-soliton tori, i.e., three-dimensional vortex solitons, with topological charges S≥1. The family with S=1 is completely stable, while the one with S=2 has alternating regions of stability and instability. The families are nearly exactly reproduced in an analytical form by the Thomas-Fermi approximation. Unstable states with S=2 and 3 split into persistently rotating pairs or triangles of unitary vortices. Application of a moderate torque to the vortex torus initiates a persistent precession mode, with the torus’ axle moving along a conical surface. A strong torque heavily deforms the vortex solitons, but, nonetheless, they restore themselves with the axle oriented according to the vectorial addition of angular momenta.

Digital Workers of the World Unite! A Framework for Critically Theorising and Analysing Digital Labour. In Special Issue: Philosophers of the World Unite! Theorising Digital Labour and Virtual Work - Definitions, Dimensions and Forms, eds. Marisol Sandoval, Christian Fuchs, Jernej A. Prodnik, Sebastian Sevignani and Thomas Allmer - Fuchs, Christian; Sandoval, Marisol (tripleC: Communication, Capitalism & Critique)

Introduction: Philosophers of the World Unite! Theorising Digital Labour and Virtual Work — Definitions, Dimensions, and Forms - Fuchs, Christian; Sandoval, Marisol; Prodnik, Jernej A.; Sevignani, Sebastian; Allmer, Thomas (tripleC: Communication, Capitalism & Critique)

Karl Marx y el estudio de los medios y la cultura hoy (Spanish translation by Roy Alfaro Vargas) - Fuchs, Christian (TELOS. Revista de Estudios Interdisciplinarios en Ciencias Sociales)

Karl Marx and the Study of Media and Culture Today - Fuchs, Christian (Culture Unbound)

WikiLeaks and the Critique of the Political Economy - Fuchs, Christian (WikiLeaks. From Popular Culture to Political Economy)

Digital Prosumption Labour on Social Media in the Context of the Capitalist Regime of Time - Fuchs, Christian (Time & Society)

Wikipedia. An Info-Communist Manifesto - Fuchs, Christian; Firer-Blaess, Sylvain (Television & New Media)

Social Networking Sites in the Surveillance Society: Critical Perspectives and Empirical Findings - Allmer, Thomas; Fuchs, Christian; Kreilinger, Verena; Sevignani, Sebastian (Media, Surveillance and Identity. Social Perspectives)

The Dialectic: Not Just the Absolute Recoil, but the World’s Living Fire that Extinguishes and Kindles Itself. Reflections on Slavoj Žižek’s Version of Dialectical Philosophy in “Absolute Recoil. Towards a New Foundation of Dialectical Materialism“ - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Thomas Piketty’s Book “Capital in the Twenty-First Century”, Karl Marx and the Political Economy of the Internet - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Revisiting the Political Economy of Communication - Fuchs, Christian; Garnham, Nicholas (tripleC: Communication, Capitalism & Critique)

Medios sociales y esfera pública [in Spanish; Social media and the public sphere] - Fuchs, Christian (Telos – Revista de Pensamiento sobre Comunicación, Tecnología y Sociedad)

Social Media and the Public Sphere [Inaugural Lecture] - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Occupy and prefiguration. A roundtable discussion - Fuchs, Christian; Wilding, Adrian; Smith, R.C.; Gunn, Richard; Ott, Michael (Heathwood Press Online)

QTube – Citizen-generated videos for Questions to the Prime Minister. Submission to the House of Commons’-Speaker’s Commission on Digital Democracy. May 19, 2014 - Fuchs, Christian

Review of Manuel Castells’ book “Networks of outrage and hope: Social movements in the Internet age“ - Fuchs, Christian (Media, Culture & Society)

Nanoporous Materials: Synthesis Concepts and Model Experiments for School Chemistry Education - Wilke, Timm; Haffer, Stefanie; Weinberger, Christian; Tiemann, Michael; Wagner, Thorsten; Waitz, Thomas (Journal of Nano Education)
Nanoporous Materials, like carbons, silica and semiconducting metal oxides, play a major role in recent scientific research, especially in the fields of energy storage, catalysis, material separation and sensor technology. Thus, our aim is to focus on simple synthesis concepts for these materials, such as soft matter templating or nanocasting, which can be easily introduced by means of appropriate models in school chemistry education or school laboratories. In addition to facile and realizable syntheses in school, several experiments concerning catalysis and gas sensing will be presented, too. By these experiments the characteristics of nanoporous materials can be obviously demonstrated and additionally, these experiments can serve as a starting point for further experiments that could easily be developed by students themselves, particularly in relation to environmental issues.

Fructose and Urea as Precursors for N-/O-Modified Mesoporous Carbon with Enhanced Sorption Capacity for Heavy Metal Ions - Weinberger, Christian; Haffer, Stefanie; Wagner, Thorsten; Tiemann, Michael (European Journal of Inorganic Chemistry)
Ordered mesoporous carbon with a high heteroatom (N, O) content was prepared by nanocasting from a melt of a eutectic mixture of fructose and urea (60/40 wt.-%; melting temperature ca. 65 °C). These precursor compounds are cheap and environmentally friendly. The material possesses enhanced pore-wall surface polarity as compared to that of mesoporous carbon prepared by the same technique without urea. This was verified by water sorption analysis. As a result, the heteroatom-modified material shows higher sorption capacity for the uptake of heavy metal ions (Cu2+) from aqueous solution, which may be interesting for potential application in wastewater cleaning.

(Dis)Like Facebook? Dialectical and Critical Perspectives on Social Media - Allmer, Thomas (Javnost – The Public: Journal of the European Institute for Communication and Culture)

Philosophers of the World Unite! Theorizing Digital Labour and Virtual Work: Definitions, Forms and Transformations

Selbstdatenschutz - Karaboga, Murat; Masur, Philipp; Matzner, Tobias; Mothes, Cornelia; Nebel, Maxi; Ochs, Carsten; Schütz, Philip; Simo Fhom, Hervais (Whitepaper des Forums Privatheit und Selbstbestimmung in der digitalen Welt)

Sicherheitsethik – Plädoyer für eine neue Bereichsethik - Matzner, Tobias; Nagenborg, Michael; Koch, Heiner (Bereichsethiken im interdisziplinären Dialog)

Anodized Aluminum as Effective and Cheap Alternative Substrate for Thermoelectric Generators - Assion, F.; Geneiß, V.; Schönhoff, M.; Hedayat, C.; Hilleringmann, Ulrich (Proceedings of the 11th European Conference on Thermoelectrics)
The wide usage of thermoelectric generators (TEG) is still blocked by very high product costs. This paper presents anodized aluminum (Al) as an effective and cheap alternative for ceramics like alumina (Al2O3) or aluminum nitride (AlN). Al has a significantly higher thermal conductivity as both named ceramics. In addition, the lower thermal stability of Al is still high enough to work with bismuth telluride based modules, which are most common. To show the advantages of the changed substrate, finite element method (FEM) simulations were performed. These simulations show that by changing the cold side substrate material the temperature drop across the substrate is reduced by 60 K. This correlates to a theoretical power gain of more than 20 {%}. Furthermore, Al can be shaped much easier than a ceramic material. The biggest advantage is obviously the price. Anodized Al is around twenty times cheaper than Al2O3. To demonstrate the easy fabrication of the proposed substrate, samples were prepared only with widely used processes like those used for conventional printed circuit boards.

A Flexible Measurement System for the Characterization of Thermoelectric Materials - Schönhoff, M.; Assion, F.; Hilleringmann, Ulrich (Proceedings of the 11th European Conference on Thermoelectrics)
The figure of merit needs to be determined to rate the quality of thermoelectric materials (TM). Therefore, it is necessary to measure all involved parameters—the Seebeck coefficient (S), the thermal conductivity ($λ$), and the electrical conductivity ($σ$).

Replacing TCO electrodes in dye sensitized solar cells by metal grids - Hilleringmann, Ulrich; Kleine, André (SPIE Proceedings)

Lithografie - Hilleringmann, Ulrich (Silizium-Halbleitertechnologie)

Random telegraph signal in nanoparticulated ZnO thin-film transistors - Vidor, FF; Wirth, GI; Hilleringmann, Ulrich (The 40th International Conference on Micro and Nano Engineering (MNE2014))

Embedded UHF RFID tag design process for rubber transmission belt using 3D model - Kanwar, Kelash; Mager, Thomas; Hilleringmann, Ulrich; Geneiss, Volker; Hedayat, Christian (2014 IEEE RFID Technology and Applications Conference (RFID-TA))

Modeling and characterization of CP-PLL phase noise in presence of dead zone - Hangmann, Christian; Wullner, Ingo; Hedayat, Christian; Hilleringmann, Ulrich (2014 IEEE 12th International New Circuits and Systems Conference (NEWCAS))

Titanium disilicide as hot side metallization layer for thermoelectric generators - Hilleringmann, Ulrich; Schonhoff, M.; Assion, F. (2013 Africon)

Händel-Solisten: Repertoire und Reisen – Betrachtungen an ausgewählten Beispielen - Höink, Dominik (Aufführungen von Händels Oratorien im deutschsprachigen Raum (1800-1900). Bibliographie der Berichterstattung in ausgewählten Musikzeitschriften)

„Der Vielgereiste ... hielt Vaterlandsliebe und -treue allzeit hoch in Ehren“. Der ,deutsche‘ Händel im Kaiserreich und in der Weimarer Republik - Höink, Dominik (Händel-Jahrbuch)

Aufführungen von Händels Oratorien im deutschsprachigen Raum (1800-1900). Bibliographie der Berichterstattung in ausgewählten Musikzeitschriften

Basic Investigations of Non-Pre-Punched Joining by Forming of Aluminium Alloy and High Strength Steel with Shear-Clinching Technology - Merklein, Marion; Meschut, Gerson; Müller, Martin; Hörhold, Réjane (Key Engineering Materials)
Facing a decreasing amount of resources on the one hand and an increasing demand for comfort on the other, more and more attention is being paid to sustainability and care for the environment. Particularly in the automotive sector, lightweight design principles continue to prosper rapidly. As a result, adjusted materials for different applications were developed. Due to the formation of intermetallic phases, most multi-material mixes cannot be welded and require adapted joining technologies. Mechanical joining technologies such as self-piercing riveting and mechanical clinching have proven effective methods of joining lightweight materials like aluminium and ductile steels. New high-strength steels are increasingly used in crash-sections, where limited deformation under impact load is required. These hot stamped steels have a very low elongation at break and therefore a low formability. Currently there is no joining by forming technology without pre-punching available using these grades of steels on die-side. The newly developed shear-clinching process is one possible method of joining this kind of material without additional elements. The fundamental idea of shear-clinching is a single-stage process in which pre-punching of the die-side material is performed by indirect shear-cutting and subsequent forming of the upper layer into this hole. This would immensely enlarge the application segment of mechanical clinching even if hot stamped steels are positioned on die-side. Fundamental studies are required to ensure process reliability and it is necessary to break down the joining process into fragments, like pre-punching and clinching with pre-punched sheet, and superpose them to form the combined procedure shear-clinching. This paper presents a detailed investigation of the sub-process clinching with pre-hole.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Der rosafarbene Elefant im Raum. Überlegungen zur fehlenden Wut über die NSA-Affäre - Shnayien, Marie-Luise (onlinejournal kultur & geschlecht)

Der rosafarbene Elefant im Raum. Überlegungen zur fehlenden Wut über die NSA-Affäre - Shnayien, Mary (onlinejournal kultur & geschlecht)
Die Politiken bebilderter Berichterstattung und die Temporalität unserer gegenwärtigen Aufmerksamkeitsökonomie betrachtend, wird den Fragen nachgegangen, wieso die Reaktionen auf die NSA-Affäre so oft von Zynismus oder Resignation gekennzeichnet sind oder sogar ganz ausbleiben, und wer eigentlich betroffen ist und reagieren sollte. Die Überlegungen sind der Versuch, die NSA-Affäre im Spannungsfeld von Technikverliebtheit und Blackboxing, den Bedingungen von Medienereignissen und Geheimdienstpraktiken, der Krise des Journalismus sowie unseren Gewohnheiten im Umgang mit der uns umgebenden rechnenden Umwelt zu situieren.

Subjektivierung als Artikulation diskursiver Ordnungen. Zur Aneignung von Subjektpositionen im Kontext der Entwicklung automatisierter Videoüberwachung - Hälterlein, Jens; Möllers , Norma; Spies, Tina (Zeitschrift für Diskursforschung)

Computing with subgroups of the modular group - Kirschmer, Markus; LEEDHAM-GREEN, CHARLES (Glasgow Mathematical Journal)
We exhibit a practical algorithm for solving the constructive membership problem for discrete free subgroups of rank 2 in PSL₂(R) or SL₂(R). This algorithm, together with methods for checking whether a two-generator subgroup of PSL₂(R) or SL₂(R) is discrete and free, have been implemented in Magma for groups defined over real algebraic number fields.
Keywords: General Mathematics

The constructive membership problem for discrete free subgroups of rank 2 of SL₂(R) - Eick, B.; Kirschmer, Markus; Leedham-Green, C. (LMS Journal of Computation and Mathematics)
We exhibit a practical algorithm for solving the constructive membership problem for discrete free subgroups of rank 2 in PSL₂(R) or SL₂(R). This algorithm, together with methods for checking whether a two-generator subgroup of PSL₂(R) or SL₂(R) is discrete and free, have been implemented in Magma for groups defined over real algebraic number fields.
Keywords: Computational Theory and Mathematics; General Mathematics

Protestantische Ruhrgebiets-Komponisten - Kulturtheologische Annäerhungen an ein disparates Phänomen - Schroeter-Wittke, Harald (Unterwegs im Experiment. Protestantische Transformationen im Ruhrgebiet)

Neue Geistliche Musik. Kulturwissenschaftliche Beobachtungen in religionspädagogischer Absicht - Schroeter-Wittke, Harald (Glaube und Lernen)

Theory of filtered type-II parametric down-conversion in the continuous-variable domain: Quantifying the impacts of filtering - Christ, Andreas; Lupo, Cosmo; Reichelt, Matthias; Meier, Torsten; Silberhorn, Christine (Physical Review A)
Parametric down-conversion (PDC) forms one of the basic building blocks for quantum optical experiments. However, the intrinsic multimode spectral-temporal structure of pulsed PDC often poses a severe hindrance for the direct implementation of the heralding of pure single-photon states or, for example, continuous-variable entanglement distillation experiments. To get rid of multimode effects narrowband frequency filtering is frequently applied to achieve a single-mode behavior. A rigorous theoretical description to accurately describe the effects of filtering on PDC, however, is still missing. To date, the theoretical models of filtered PDC are rooted in the discrete-variable domain and only account for filtering in the low-gain regime, where only a few photon pairs are emitted at any single point in time. In this paper we extend these theoretical descriptions and put forward a simple model, which is able to accurately describe the effects of filtering on PDC in the continuous-variable domain. This developed straightforward theoretical framework enables us to accurately quantify the tradeoff between suppression of higher-order modes, reduced purity, and lowered Einstein–Podolsky–Rosen entanglement, when narrowband filters are applied to multimode type-II PDC.

Phase-locked multi-THz high-harmonic generation by dynamical bloch oscillations in bulk semiconductors - Meier, Torsten; Hohenleutner, M.; Schubert, O.; Langer, F.; Urbanek, B.; Lange, C.; Huttner, U.; Golde, D.; Kira, M.; Koch, S.W.; Huber, R. (19th International Conference on Ultrafast Phenomena)
Ultra-intense and CEP-stable waveforms in the multi-THz range control dynamical Bloch oscillations and interband polarization in bulk GaSe, leading to the emission of all-coherent high-order harmonics covering 12.7 optical octaves from THz to VIS regimes.

Nonlinear dynamics of Airy-vortex 3D wave packets: emission of vortex light waves - Driben, Rodislav; Meier, Torsten (Optics Letters)
The dynamics of 3D Airy-vortex wave packets is studied under the action of strong self-focusing Kerr nonlinearity. Emissions of nonlinear 3D waves out of the main wave packets with the topological charges were demonstrated. Because of the conservation of the total angular momentum, charges of the emitted waves are equal to those carried by the parental light structure. The rapid collapse imposes a severe limitation on the propagation of multidimensional waves in Kerr media. However, the structure of the Airy beam carrier allows the coupling of light from the leading, most intense peak into neighboring peaks and consequently strongly postpones the collapse. The dependence of the critical input amplitude for the appearance of a fast collapse on the beam width is studied for wave packets with zero and nonzero topological charges. Wave packets carrying angular momentum are found to be much more resistant to the rapid collapse.

Coupled Airy breathers - Driben, R.; Konotop, V. V.; Meier, Torsten (Optics Letters)
The dynamics of two component-coupled vectorial Airy beams is investigated. In the linear propagation regime, a complete analytic solution describes the breather-like propagation of two components that feature nondiffracting self-accelerating Airy behavior. The superposition of two beams with different input properties opens the possibility of designing more complex nondiffracting propagation scenarios. In the strongly nonlinear regime, the dynamics remain qualitatively robust as is revealed by direct numerical simulations. Because of the Kerr effect, the two beams emit solitonic breathers whose coupling period is compatible with the remaining Airy-like beams. The results of this study are relevant for the description of photonic and plasmonic beams that propagate in coupled planar waveguides, as well as for birefrigent or multiwavelength beams.

Rilkes Stundenbuch. Neu erhört und zur Sprache gebracht (Gotthard Fermor (Hg.): Rainer Maria Rilke: Das Stunden-Buch. Erstes Buch: Das Buch vom Mönchischen Leben. Mit 2 Audio-CDs, Gütersloh 2014) - Schroeter-Wittke, Harald (Magazin für Theologie und Ästhetik. http://www.theomag.de/92/hsw18.htm)

Siegfried Eckert: 2017. Zweitausendsiebzehn. Reformation statt Reförmchen. Eine Streitschrift zur Lage der Ev. Kriche ind Deutschland, Gütersloh 2014 - Schroeter-Wittke, Harald (Magazin für Theologie und Ästhetik. http://www.theomag.de/91/hsw17.htm)

Tag des Erzengels Michael und aller Engel - Michaelistag (29.9.2014). Hebr 1,7.13-14: Vom Genuss englischer Dienstleistungen - Schroeter-Wittke, Harald (Göttinger Predigtmeditationen)

15. Sonntag nach Trinitatis. 1. Mose 2,4b-9(10-14)15: Unterwegs nach Eden - Schroeter-Wittke, Harald; Kirsner, Inge (Predigtstudien VI/2)

Engineering plasmonic and dielectric directional nanoantennas - Hildebrandt, Andre; Reichelt, Matthias; Meier, Torsten; Förstner, Jens (Ultrafast Phenomena and Nanophotonics XVIII)
Optical and infrared antennas provide a promising way to couple photons in and out of nanoscale structures. As counterpart to conventional radio antennas, they are able to increase optical felds in sub-wavelength volumes, to enhance excitation and emission of quantum emitters or to direct light, radiated by quantum emitters. The directed emission of these antennas has been mainly pursued by surface plasmon based devices, e.g. Yagi-Uda like antennas, which are rather complicated due to the coupling of several metallic particles. Also, like all metallic structures in optical or infrared regime, these devices are very sensitive to fabrication tolerances and are affected by strong losses. It has been shown recently, that such directed emission can be accomplished by dielectric materials as well. In this paper we present an optimization of nanoscopic antennas in the near infrared regime starting from a metallic Yagi-Uda structure. The optimization is done via a particle-swarm algorithm, using full time domain finite integration simulations to obtain the characteristics of the investigated structure, also taking into account substrates. Furthermore we present a dielectric antenna, which performs even better, due to the lack of losses by an appropriate choice of the dielectric material. These antennas are robust concerning fabrication tolerances and can be realized with different materials for both the antenna and the substrate, without using high index materials.
Keywords: tet_topic_opticalantenna

Influence of Coulomb-induced band couplings on linear excitonic absorption spectra of semiconducting carbon nanotubes - Liu, Hong; Schumacher, Stefan; Meier, Torsten (Physical Review B)
Starting from the extended Su-Schrieffer-Heeger model, multiband semiconductor Bloch equations are formulated in momentum space and applied to the analysis of the linear optical response of semiconducting carbon nanotubes (SCNTs). This formalism includes the coupling of electron-hole pair excitations between different valence and conduction bands, originating from the electron-hole Coulomb attraction. The influence of these couplings, which are referred to as nondiagonal interband Coulomb interaction (NDI-CI), on the linear excitonic absorption spectra is investigated and discussed for light fields polarized parallel to the tube direction. The results show that the intervalley NDI-CI leads to a significant increase of the band gap and a decrease of the exciton binding energy that results in a blueshift of the lowest-frequency excitonic absorption peak. The strength of these effects depends on the symmetry of the SCNT. Furthermore, for zigzag SCNTs with higher symmetry other nonintervalley NDI-CI terms also affect the spectral positions of excitonic absorption peaks.

Regeneration of Airy pulses in fiber-optic links with dispersion management of the two leading dispersion terms of opposite signs - Driben, R.; Meier, Torsten (Physical Review A)
Dispersion management of periodically alternating fiber sections with opposite signs of two leading dispersion terms is applied for the regeneration of self-accelerating truncated Airy pulses. It is demonstrated that for such a dispersion management scheme, the direction of the acceleration of the pulse is reversed twice within each period. In this scheme the system features light hot spots in the center of each fiber section, where the energy of the light pulse is tightly focused in a short temporal slot. Comprehensive numerical studies demonstrate a long-lasting propagation also under the influence of a strong fiber Kerr nonlinearity.

Reformation statt Reförmchen - Schroeter-Wittke, Harald (Der Kirchentag. Das Magazin)

Medienkompetenzwahrnehmung im Migrationskontext: Empirische Ergebnisse aus der Frühen Bildung bei türkischen und deutschen Kindern - Marci-Boehncke, Gudrun; Rath, Matthias (Frühe Bildung)
Medienerfahrungen gehören zum kindlichen Alltag, doch die familialen Bedingungen medialen Lernens sind unterschiedlich. Die öffentlichen Bildungsinstitutionen sollen daher kompensatorisch wirken, um allen Kindern gleiche Chancen vor und für den Schulbeginn zu sichern. Dies gilt besonders im Kontext unserer Zuwanderungsgesellschaft, wo Kinder mit verschiedenen kulturellen Hintergründen aufwachsen. Im Fokus unseres Berichts steht ein Interventions- und Forschungsprojekt in Dortmund, wo über 60 % der Kinder in Einrichtungen der Frühen Bildung verschiedenkulturelle Familienhintergründe mitbringen. In Einzelmaßnahmen, in denen Medienbildung an weitere inhaltliche Bildungsaspekte und Themen angebunden ist, üben Kinder aus verschiedenen Herkunftskulturen gemeinsam das Produzieren und Kommunizieren mit und über Medien. Die Arbeit in den Kitas wird trianguliert evaluiert und Erzieherinnen wie Eltern werden über die Wahrnehmung der Kinder sowie den familiären Medienumgang befragt. Aus diesem Datenpool sollen hier Ergebnisse vorgestellt werden, wie türkische Kinder als größte Migrantengruppe in ihrer Medienkompetenz in den Familien und in der Kita wahrgenommen werden – wobei sich je nach Perspektive auffällige Unterschiede in der elterlichen und der professionellen Wahrnehmung kindlicher Medienkompetenz zeigen, sowohl genderspezifisch als auch kulturspezifisch.

Gier - Zur Kapitalismuskritik in "Johann Holtrop" von Rainald Goetz und in "Gesellschaft mit beschränkter Haftung" von Nora Bossong - Müller, Inez (Leitkulturen und Wertediskussionen)

Analytic moduli spaces of simple sheaves on families of integral curves - Burban, Igor; Kreußler, B. (Mathematische Nachrichten)

Bild- und Medientheorien der Naturwissenschaften: Epistemologische Effektivität von Visualisierungen in der Astronomie - Adelmann, Ralf (Visualität, Kultur und Gesellschaft)